JUSTICE AGAINST «LAW AND ECONOMICS» - Ilya, Ruzanov (European Scientific Journal, ESJ, 2015)
The main issue of the paper is the problem of adaptivity of «law and economics» as universal doctrine. For example some cultural specificity of Russia put barriers on the development of economic analysis of law in the country. However it pointed in that all problems are not crucial and there are some tools to solve it. The most popular argument against the «law and economics» is that efficiency which is the main category of this field, sometime contradicts Justice as the main category of law. Nevertheless it was proved that there is no «gap» between Justice and efficiency. Another problem of «law and economics» in some countries is the doubtfulness of rational behavior assumption which is very important part of «law and economics». Although some oncoming investigations of this theme are required, it does not look as a big problem. The conclusion is that economics analysis of law is a science field which is universal, although it can be some variations because of national specificity.